Pomegranate, its Components, and Modern Deliverable Formulations as Potential Botanicals in the Prevention and Treatment of Various Cancers - Hussein, Laila; Gouda, Mostafa; Buttar, Harpal S. (Current Drug Delivery, 2021)
Cancer is a global multifactorial disease consisting of over 200 types of cancers. It is well recognized that primary prevention is an effective way to fight cancers by using natural polyphenolic anticancer foods, vegetables, and fruits, avoiding exposure to the carcinogenic environment, smoking cessation, and through lifestyle modifications. The present review provides up-todate information on the effects and functions of pomegranate juice and its bioactive components on the most widespread six cancer types. Pomegranate contains important polyphenolic compounds, such as ellagitannins and punicalagin, with strong antioxidant ability for scavenging free radicals and producing metal-chelates in the biological tissues. The in vitro and in vivo studies suggests that antioxidant and anti-inflammation properties of pomegranate constitute have major antimutagenic and antiproliferative activities for regulating gene expression, modulating cellular mechanisms, and limiting the ability of cancers to metastasize. A limited number of clinical studies have suggested that pomegranate ingredients have the potential for the prevention and treatment of cancer, especially colorectal and prostate cancer. In cancer therapy, it remains a clinical dilemma to hit the right target without inducing side effects. The costly anticancer chemotherapies are often associated with drug resistance and serious side effects in vital organs and noncancerous neighboring cells. It appears that the pomegranate-based phytotherapy would be affordable and cost-effective for next-generation non-pharmacologic anticancer remedies with lesser side effects. However, well-designed, randomized, double-blind, and multi-center studies are needed to establish the long-term safety, efficacy, and dose schedules for orally deliverable pomegranate formulations.
Keywords: apoptosis induction